AN ANALYSIS OF THE EFFECTIVENESS OF INTEREST RATES TO FACILITATE PRICE STABILITY AND ECONOMIC GROWTH IN SOUTH AFRICA - MEYER, Danie Francois; CHIPETA, Chama; CAMEL, Richard Thabang Mc (Studia Universitatis Babeș-Bolyai Oeconomica, 2018)
Price stability supports accelerated economic growth (GDP), thus the main objective of most central banks is to ensure price stability. The South African economy is experiencing a unique monetary policy dilemma, where a high inflation rate is accompanied by high interest rates and low GDP. This is an unconventional monetary policy scenario and may hold strenuous repercussions for the South African economy. This dilemma was held as the rationale behind this study. The study investigated the effectiveness of the use of the repo rate as an instrument to facilitate price stability and GDP in South Africa. Long-run, short-run and casual relationships between interest rates, inflation and GDP were therefore analyzed. The methodology is based on an econometric process which included a Johansen co-integration test, with a Vector Error Correction model (VECM). Casual relationships were also tested using Granger causality tests. Results of the Johansen Co-integration test indicated the presence of co-integrating long-run relationships between the variables and a significant and negative long-run relationship between the repo rate and inflation rate was revealed, whereas GDP and inflation rate exhibited a significant and positive long-run relationship. The study also found short-run relationships between inflation and GDP, but not for inflation and the repo rate. Further areas of potential research may fixate towards the assessment of other significant alternative policy tools which may be utilized by various countries’ monetary policy authorities to influence supply specific inflationary pressures led by the cost-push phenomena, especially in the short-run. JEL classification: E65, O11, O55;